Deciphering mechanisms of drug sensitivity and resistance to Selective Inhibitor of Nuclear Export (SINE) compounds. Issue 1 (December 2015) - Crochiere, Marsha; Kashyap, Trinayan; Kalid, Ori; Shechter, Sharon; Klebanov, Boris; Senapedis, William; Saint-Martin, Jean-Richard; Landesman, Yosef
Abstract Background Exportin 1 (XPO1) is a well-characterized nuclear export protein whose expression is up-regulated in many types of cancers and functions to transport key tumor suppressor proteins (TSPs) from the nucleus. Karyopharm Therapeutics has developed a series of small-molecule Selective Inhibitor of Nuclear Export (SINE) compounds, which have been shown to block XPO1 function both in vitro and in vivo. The drug candidate, selinexor (KPT-330), is currently in Phase-II/IIb clinical trials for treatment of both hematologic and solid tumors. The present study sought to decipher the mechanisms that render cells either sensitive or resistant to treatment with SINE compounds, represented by KPT-185, an early analogue of KPT-330. Methods Using the human fibrosarcoma HT1080 cell line, resistance to SINE was acquired over a period of 10 months of constant incubation with increasing concentration of KPT-185. Cell viability was assayed by MTT. Immunofluorescence was used to compare nuclear export of TSPs. Fluorescence activated cell sorting (FACS), quantitative polymerase chain reaction (qPCR), and immunoblots were used to measure effects on cell cycle, gene expression, and cell death. RNA from naïve and drug treated parental and resistant cells was analyzed by Affymetrix microarrays. Results Treatment of HT1080 cells with gradually increasing concentrations of SINE resulted in > 100 fold decrease in sensitivity to SINE cytotoxicity. Resistant cells displayed prolonged cell cycle, reduced nuclear accumulation of TSPs, and similar changes in protein expression compared to parental cells, however the magnitude of the protein expression changes were more significant in parental cells. Microarray analyses comparing parental to resistant cells indicate that a number of key signaling pathways were altered in resistant cells including expression changes in genes involved in adhesion, apoptosis, and inflammation. While the patterns of changes in transcription following drug treatment are similar in parental and resistant cells, the extent of response was more robust in the parental cells. Conclusions These results suggest that SINE resistance is conferred by alterations in signaling pathways downstream of XPO1 inhibition. Modulation of these pathways could potentially overcome the resistance to nuclear export inhibitors.